Progress in Metabolic Studies of Gastric Cancer and Therapeutic Implications - Romo-Perez, Adriana; Dominguez-Gomez, Guadalupe; Chavez-Blanco, Alma; Taja-Chayeb, Lucia; Gonzalez-Fierro, Aurora; Diaz-Romero, Consuelo; Lopez-Basave, Horacio N.; Duenas-Gonzalez, Alfonso (Current Cancer Drug Targets, 2022)
Background: Worldwide, gastric cancer is ranked the fifth malignancy in incidence and the third malignancy in mortality. Gastric cancer causes an altered metabolism that can be therapeutically exploited. Objective: The objective of this study is to provide an overview of the significant metabolic alterations caused by gastric cancer and propose a blockade. Methods: A comprehensive and up-to-date review of descriptive and experimental publications on the metabolic alterations caused by gastric cancer and their blockade. This is not a systematic review. Results: Gastric cancer causes high rates of glycolysis and glutaminolysis. There are increased rates of de novo fatty acid synthesis and cholesterol synthesis. Moreover, gastric cancer causes high rates of lipid turnover via fatty acid β-oxidation. Preclinical data indicate that the individual blockade of these pathways via enzyme targeting leads to antitumor effects in vitro and in vivo. Nevertheless, there is no data on the simultaneous blockade of these five pathways, which is critical as tumors show metabolic flexibility in response to the availability of nutrients. This means tumors may activate alternate routes when one or more are inhibited. We hypothesize there is a need to simultaneously block them to avoid or decrease the metabolic flexibility that may lead to treatment resistance. Conclusion: There is a need to explore the preclinical efficacy and feasibility of combined metabolic therapy targeting the pathways of glucose, glutamine, fatty acid synthesis, cholesterol synthesis, and fatty acid oxidation. This may have therapeutical implications because we have clinically available drugs that target these pathways in gastric cancer.
Keywords: lipidic